A water-stable Zn4O-based MOF decorated with carbazolyl chromophores for multi-responsive fluorescence sensing of Fe3+, Cr2O72− and nitro-compounds. (20th September 2022) - Ding, Shan; Cheng, Cong; Xu, Jia-Hui; Tang, Zhe; Yang, Guang-Sheng; Peng, Shuai-Feng; Yu, Lin-Qun; Jiang, Chun-Jie; Su, Zhong-Min
Abstract : A MOF with strong deep blue light emission and high quantum efficiency has high selectivity and sensitivity for detecting 2, 6-dichloro-4-nitroaniline. Abstract : A novel luminescent isoreticular metal–organic framework Zn4 O(ECMTDC)3 ·10DMF (Cz-MOF-1 ), where ECMTDC denotes 3-(9-ethyl-9 H -carbazol-3-yl)-4-methylthieno[2, 3- b ]thiophene-2, 5-dicarboxylate and DMF denotes N, N -dimethylformamide, was successfully synthesized via solvothermal methods from Zn(NO3 )2 ·6H2 O and H2 ECMTDC in DMF. Powder X-ray diffraction experiments along with scanning electron microscopy images indicate that Cz-MOF-1 has excellent water stability compared with other Zn4 O-based MOFs, which can be attributed to the hydrophobic surroundings around the Zn4 O clusters formed from N -ethylcarbazolyl and methyl groups. Cz-MOF-1 displays a strong deep blue light emission (452 nm) and a quantum efficiency of 3.74%, and has high selectivity and sensitivity for the detection of Fe 3+, Cr2 O7 2− and DCN. Furthermore, the possible luminescence sensing mechanisms have been discussed in detail, which are supported by PXRD analysis, UV-vis spectroscopy and density functional theory (DFT).